2008
DOI: 10.1007/s10832-008-9478-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mg dopant on the degradation of InGaN multiple quantum wells in AlInGaN-based light emitting devices

Abstract: We investigated the effects of Mg dopant on the degradation of AlInGaN-based light emitting diodes (LEDs) and laser diodes (LDs) with InGaN multi-quantum wells (MQWs). Photoluminescence (PL) intensity of InGaN MQWs was significantly decreased with increasing the Mg intentional doping process in InGaN active region, indicating that Mg dopant could degrade the optical quality of InGaN MQWs. From secondary ion mass spectroscopy (SIMS) analysis of AlInGaN-based LDs grown on GaN/ sapphire and GaN substrate with dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Meneghni et al [33] reported that generation defects and doping redistribution in the active region would degrade the power output and increase the reverse leakage current of UV LEDs during electrical aging. Reports presented evidence for the diffusion of doping/impurities (e.g., Mg and Si) toward the active region of LEDs [34], [35] and suggested that the presence of TDs play a significant role in easing the diffusion process even at relatively low temperatures [33]. Therefore, the improved reliability of UV LEDs with ex situ AlN nucleation layer can again be attributed to the improved crystal quality of the GaN and n-AlGaN by the sputtered AlN nucleation layer.…”
Section: Methodsmentioning
confidence: 99%
“…Meneghni et al [33] reported that generation defects and doping redistribution in the active region would degrade the power output and increase the reverse leakage current of UV LEDs during electrical aging. Reports presented evidence for the diffusion of doping/impurities (e.g., Mg and Si) toward the active region of LEDs [34], [35] and suggested that the presence of TDs play a significant role in easing the diffusion process even at relatively low temperatures [33]. Therefore, the improved reliability of UV LEDs with ex situ AlN nucleation layer can again be attributed to the improved crystal quality of the GaN and n-AlGaN by the sputtered AlN nucleation layer.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 5 shows the typical current-voltage characteristics of LEDs obtained before and after stress time of 300 h. It is shown that the forward and reverse leakage currents increase with increasing stress time. Note that the evolution of leakage currents becomes more significant at the elevated temperatures [25], [26], [27], [28], [29]. This indicates that the nonradiative recombination defects are more generated with ambient temperatures.…”
Section: Methodsmentioning
confidence: 93%
“…An optimal thickness value of u-GaN interlayer is determined with which InGaN LD device has the highest output light power under the same current injection condition. Besides, when the value of background concentration of u-GaN interlayer is raised from 5×10 15 cm −3 to a high value such as 5×10 18 cm −3 , the width of depletion region on n-side may become too small to cover the whole MQW active region and the output light power is then deteriorated. The simulation results demonstrate that for the InGaN LD with a fixed thickness value of u-GaN interlayer, the optimal value of background concentration, which corresponds to the highest output light power of InGaN LDs, decreases with increasing u-GaN interlayer thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of inserting an unintentionally doped GaN interlayer between MQW active region and Al 0.2 Ga 0.8 N EBL is that it can block the possible Mg diffusion from p-doped region into MQW active region during the epitaxial growth of InGaN LD materials in metal organic chemical vapor deposition (MOCVD) system. 14,15 If the p-doped Al 0.2 Ga 0.8 N EBL locates next to the last quantum barrier of GaN thin layer, Mg dopant may easier diffuse into MQW active region and lead to a formation of nonradiative recombination centers. The inserted u-GaN interlayer pushes all of the p-doped layers far away from MQW active region and thus prevents the possible detrimental effects of high-level Mg doping and impurity diffusion.…”
Section: -4mentioning
confidence: 99%